Early childhood students' perceptions of studying by distance learning for the Diploma of Teaching (ECE) - June Kean (Journal of Open, Flexible and Distance Learning, 2012)
Traditionally, tertiary teacher education has been delivered in New Zealand through face-to-face teaching courses with students listening and taking notes while receiving instruction from a lecturer. Interaction between lecturer and students in a classroom setting has been considered a vital component in this process.